ORGANISATIONAL DETERMINANTS INFLUENCING INFORMATION SYSTEMS REIMPLEMENTATION: SOME IMPLICATIONS TO THE DEVELOPING COUNTRIES - Sayyen Teoh; Mohamad Jais; Ayoib Che Ahmad; Syed Nasirin (Asian Academy of Management Journal, 2010)
This article presents an in-depth study of global Web-based Marketing Decision Support System reimplementation, in a British-based Fast Moving Consumer Goods (FMCG) manufacturer. The paper shows that the success of a system implementation can still be marginal even if the organisation understands the key organisational determinants of success and has influence over them. The paper concludes with a discussion of how implementation planning, user need analysis and communication problems could be overcomed and also some implications to the companies in the developing nations.